Effect of Sowing Dates and Weed Management Practices on Yield Attributes of Summer Sesame (Sesamum indicum L.) - , J. Rakesh; , B.C Patra; , P. Bandhopadhay; , S.K. Dey; , S. Banerjee (Archives of Current Research International, 2025)
The present study aimed to determine the Effect of Dates of Sowing and Weed Management Practices on Summer Sesame in the New Alluvial Zone of West Bengal to explore the optimal strategies for weed control and improve sesame yield. The appropriate sowing date is a crucial factor in aligning plant growth stages with environmental conditions to achieve optimal yield. Sesame, known for its drought tolerance, is primarily grown as a dryland crop, particularly in the Indian subcontinent. A field experiment was conducted during the summer season of 2022 and 2023 at Instructional farm, Jaguli, Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, West Bengal. The soil of the experimental site was clay loam in texture, near neutral in reaction (pH: 6.5) and non-saline (EC 0.3); medium in organic carbon (0.68%), low available nitrogen (196.76 kg ha-1) and high in available phosphorus (24 P2O5 kg ha-1) and available potassium (294.5 K2O kg ha-1). The experiment was laid out in split plot design having dates of sowing i.e. D1: February 21st, D2: March 7th, and D3: March 22nd in main plot and Sub plot treatments comprised of weed management practices i.e. W1- Pendimethalin @ 1 kg a.i. ha-1 [2 DAS (days after sowing)] + Hand weeding (30 DAS),W2- Butachlor@ 1kga.i. ha-1(2 DAS)+Hand weeding(30 DAS),W3- Hand weeding(15DAS)+ Quizalofop ethyl @ 50 g a.i. ha-1 (30 DAS), W4- Pendimethalin @ 1 kg a.i.ha-1 (2 DAS) + Quizalofop ethyl @ 50 ga.i. ha-1 (30 DAS), W5- Butachlor @ 1 kg a.i.ha-1 (2 DAS) + Quizalofop ethyl @ 50 g a.i. ha-1 (30 DAS),W6- Hand weeding (15 DAS) + Hand weeding(30DAS),W7-Weedycheck and W8-Weed free check and replicated thrice. The sesame variety ‘Savitri’ was chosen for the experiment. The yield attributes and yield associated characters like number of branches plant-1, number of capsules plant-1, number of seeds capsule-1 and number of seeds plant-1 were significantly influenced by dates of sowing and weed management practices; however, 1000 seed weight (test weight) was not influenced by dates of sowing and weed management practices. Sowing on 7th March (D2) recorded a significantly higher number of branches plant-1(6.26), number of capsules plant-1 (52.97), number of seeds capsule-1 (45.74) and number of seeds plant-1(2137.37). Among weed management treatments, weed-free check (W8) inscribed significantly more number of branches plant-1(8.12), number of capsules plant-1(58.13), number of seeds capsule-1 (50.12) and number of seeds plant-1 (2462.36 and 2232.96) and it was at par with Pendimethalin @ 1 kg a.i. ha-1 (2 DAS) + Hand weeding (30 DAS) i.e. W1. No significant effect had been observed among the interactions with respect to the yield attributing characters. Determining the optimal sowing time, which enhances the efficient use of the land area, along with selecting a cultivar that offers a high average yield, is a key factor in ensuring a profitable return from sesame cultivation.